2013
DOI: 10.3748/wjg.v19.i39.6651
|View full text |Cite
|
Sign up to set email alerts
|

Importance ofbvalue in diffusion weighted imaging for the diagnosis of pancreatic cancer

Abstract: Low b value images demonstrated superior anatomical details when compared to high b value images. Tumor tissue definition was high and contrast with the surrounding tissues was good. DWI was useful in diagnosing pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For example, Yoshikawa et al reported that pancreatic cancer had a higher ADC value than normal pancreas [ 34 ] while some studies showed no significant difference in ADC values between pancreatic tumor and normal pancreatic parenchyma [ 35 , 36 , 37 , 38 ]. However, an increased body of evidence have shown that ADC values of PDAC are much lower than those of normal pancreas [ 10 , 31 , 39 , 40 ]. Interestingly, in the present study we have demonstrated a significant increase in ADC in the advanced stages of PDAC tumor.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yoshikawa et al reported that pancreatic cancer had a higher ADC value than normal pancreas [ 34 ] while some studies showed no significant difference in ADC values between pancreatic tumor and normal pancreatic parenchyma [ 35 , 36 , 37 , 38 ]. However, an increased body of evidence have shown that ADC values of PDAC are much lower than those of normal pancreas [ 10 , 31 , 39 , 40 ]. Interestingly, in the present study we have demonstrated a significant increase in ADC in the advanced stages of PDAC tumor.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to perform a meta-analysis in the subgroup of studies since 50% of the studies did not report any b-values. While a high intensity signal with poor anatomical delineation was associated with a high b-value of 1100 s/mm 2 , benign and malignant pancreatic tumors could be distinguished with a b-value of 700 s/mm 2 associated with ADCs; b-values of 50, 350, 400, 450, and 1100 s/mm 2 were associated with imprecise ADC values and could not differentiate between benign and malignant tumors (50). A b-value of 800 s/mm 2 can help to differentiate between pancreatic cancer, mass-forming focal pancreatitis, and a normal pancreas (51).…”
Section: Discussionmentioning
confidence: 99%
“…In general, cancers, including pancreatic cancer, tend to show higher signal intensity on DWI with a lower ADC value than normal tissues because cancer tissues have several factors restricting the water diffusion, such as higher cellularity, tissue disorganization, and extracellular space tortuosity [ 85 ]. In particular, in the DWI technique, the histology of different targets varies according to the b-values used, which reflect the strength and timing of the gradients used to generate these particular images [ 86 ]. DWI and ADCs with small b-values are generally not very useful in diagnosing malignant tumors since the proportion of diffusion is small and blood perfusion has a greater impact on the final imaging result [ 87 ].…”
Section: The Additional Value Of Diffusion-weighted Imaging: Can It R...mentioning
confidence: 99%